Selectins-The Two Dr. Jekyll and Mr. Hyde Faces of Adhesion Molecules-A Review - Tvaroška, Igor; Selvaraj, Chandrabose; Koča, Jaroslav (Molecules (Basel, Switzerland), 2020)
Selectins belong to a group of adhesion molecules that fulfill an essential role in immune and inflammatory responses and tissue healing. Selectins are glycoproteins that decode the information carried by glycan structures, and non-covalent interactions of selectins with these glycan structures mediate biological processes. The sialylated and fucosylated tetrasaccharide sLex is an essential glycan recognized by selectins. Several glycosyltransferases are responsible for the biosynthesis of the sLex tetrasaccharide. Selectins are involved in a sequence of interactions of circulated leukocytes with endothelial cells in the blood called the adhesion cascade. Recently, it has become evident that cancer cells utilize a similar adhesion cascade to promote metastases. However, like Dr. Jekyll and Mr. Hyde's two faces, selectins also contribute to tissue destruction during some infections and inflammatory diseases. The most prominent function of selectins is associated with the initial stage of the leukocyte adhesion cascade, in which selectin binding enables tethering and rolling. The first adhesive event occurs through specific non-covalent interactions between selectins and their ligands, with glycans functioning as an interface between leukocytes or cancer cells and the endothelium. Targeting these interactions remains a principal strategy aimed at developing new therapies for the treatment of immune and inflammatory disorders and cancer. In this review, we will survey the significant contributions to and the current status of the understanding of the structure of selectins and the role of selectins in various biological processes. The potential of selectins and their ligands as therapeutic targets in chronic and acute inflammatory diseases and cancer will also be discussed. We will emphasize the structural characteristic of selectins and the catalytic mechanisms of glycosyltransferases involved in the biosynthesis of glycan recognition determinants. Furthermore, recent achievements in the synthesis of selectin inhibitors will be reviewed with a focus on the various strategies used for the development of glycosyltransferase inhibitors, including substrate analog inhibitors and transition state analog inhibitors, which are based on knowledge of the catalytic mechanism.
Keywords: cancer; Neoplasm Proteins; Cell Adhesion; Inflammation; Leukocytes; inhibitors; nádorové proteiny; rolling leukocytů; selectin-ligand interactions; zánět; sialyl Lewis x; inflammation; glycosyltransferases; transition state analog inhibitors; Leukocyte Rolling; selectin ligands; Neoplasms; selectins; zvířata; Humans; nádory; Selectins; buněčná adheze; carbohydrate determinants; leukocyty; lidé; selektiny; Animals